Personal Reflections on Unangax̂ (Aleut) Men and Matriculture: Transcript - Price, Carter (Matrix, 2025)
In this recorded interview, Carter Price shares his thoughts about being an Unangax̂ (Aleut) man and what that means, as well as exploring the role of Unangax̂ men in the lives of Unangax̂ women. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Unangax̂ (Aleut) Men and Matriculture, Carter Price